Späte Subjekte: Skizze einer perimortalen Eschatologie im ethischen Interesse - Moos, Thorsten (Zeitschrift für Theologie und Kirche, 2023)
A widely overlooked topic of eschatology is examined: the perimortal realm, which - contrary to what definitions of the time of death suggest - is in many respects not characterised by a clear cut, but by a phenomenal continuum. In particular, elements of vital, personal and individual subjecthood point beyond death. It is the task of eschatology to interpret the partly contradictory experiences associated with this, which thus also opens up a multitude of ethically relevant aspects of perimortal situations.